2015
DOI: 10.1016/j.eneco.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Economics of co-firing coal and biomass: An application to Western Canada

Abstract: Co-firing biomass and coal in retrofitted power plants is an efficient means to reduce carbon dioxide emissions in the energy sector. Under IPCC reporting rules, the impacts of energy produced from biomass would not be reported in the energy sector, thereby effectively lowering the emissions intensity of a power plant. In this study, a carbon tax is compared to a feed-in tariff for incentivizing conversion of coal plants to co-fire with biomass. In the application, a model of the Alberta electrical grid with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Although the health benefits in China could be different, it still demonstrates the potential of pelletized blends on the reduction of carbonaceous particles. Besides, the approach can decrease emissions of other gases and particles like CO 2 , SO 2 , NO x , EC etc, and avoid the methane leakage problem which is commonly accompanied with biogas technology (Sami et al, 2001;Johnston and van Kooten, 2015). If the energy density of biomass pellets is equivalent to medium coal as Zeng et al (2007) reported, utilization of pelletized blends as energy may not only provide a basis for airborne pollutants control, but also meets the demands for energy in rural China.…”
Section: Implications On Residential Biofuel Usementioning
confidence: 99%
See 1 more Smart Citation
“…Although the health benefits in China could be different, it still demonstrates the potential of pelletized blends on the reduction of carbonaceous particles. Besides, the approach can decrease emissions of other gases and particles like CO 2 , SO 2 , NO x , EC etc, and avoid the methane leakage problem which is commonly accompanied with biogas technology (Sami et al, 2001;Johnston and van Kooten, 2015). If the energy density of biomass pellets is equivalent to medium coal as Zeng et al (2007) reported, utilization of pelletized blends as energy may not only provide a basis for airborne pollutants control, but also meets the demands for energy in rural China.…”
Section: Implications On Residential Biofuel Usementioning
confidence: 99%
“…Co-firing is another efficient means recommended in energy sector, due to its high potential for commercialization and the emission reduction of CO, CO 2 , SO 2 and NO x in most co-firing of biomass and coal tests (Sami et al, 2001;Johnston and van Kooten, 2015). In this study, bulk corn stover, pelletized corn stover (pellet Fig.…”
Section: Influence Of Stoves Biofuel Pellets and Co-firingmentioning
confidence: 99%
“…In Europe and the United States of America biomass is largely used either on a domestic scale or on an industrial scale such as large thermoelectric power stations [11].…”
Section: Pelletsmentioning
confidence: 99%
“…One can convert a coal plant to function with biomass, thereby reducing carbon dioxide emissions, or to create an original biomass power plant [11], [12].…”
Section: Pelletsmentioning
confidence: 99%
“…Akhtari et al (Akhtari, Sowlati, & Day, 2014), Schmidt et al (Schmidt, Leduc, Dotzauer, Kindermann, & Schmid, 2010), Steubing et al (Steubing, Zah, & Ludwig, 2012), Chau et al (Chau, Sowlati, Sokhansanj, Preto, Melin, & Bi, 2009), Johnston and Kooten (Johnston & Kooten, 2015). Groscurth et al (Groscurth, Almeida, De, Bauen, Costa, & Ericson, 2000) provided a comprehensive analysis of the economic and environmental performance of the energy use of biomass for selected existing facilities.…”
Section: Literature Reviewmentioning
confidence: 99%